Inferring transient dynamics of human populations from matrix non‐normality. Issue 1 (5th June 2018) - Nicol‐Harper, Alex; Dooley, Claire; Packman, David; Mueller, Markus; Bijak, Jakub; Hodgson, David; Townley, Stuart; Ezard, Thomas
Abstract: In our increasingly unstable and unpredictable world, population dynamics rarely settle uniformly to long‐term behaviour. However, projecting period‐by‐period through the preceding fluctuations is more data‐intensive and analytically involved than evaluating at equilibrium. To efficiently model populations and best inform policy, we require pragmatic suggestions as to when it is necessary to incorporate short‐term transient dynamics and their effect on eventual projected population size. To estimate this need for matrix population modelling, we adopt a linear algebraic quantity known as non‐normality. Matrix non‐normality is distinct from normality in the Gaussian sense, and indicates the amplificatory potential of the population projection matrix given a particular population vector. In this paper, we compare and contrast three well‐regarded metrics of non‐normality, which were calculated for over 1000 age‐structured human population projection matrices from 42 European countries in the period 1960 to 2014. Non‐normality increased over time, mirroring the indices of transient dynamics that peaked around the millennium. By standardising the matrices to focus on transient dynamics and not changes in the asymptotic growth rate, we show that the damping ratio is an uninformative predictor of whether a population is prone to transient booms or busts in its size. These analyses suggest that population ecology approaches to inferring transient dynamics have too often relied on suboptimal analytical tools focussed on an initial population vector rather than the capacity of the life cycle to amplify or dampen transient fluctuations. Finally, we introduce the engineering technique of pseudospectra analysis to population ecology, which, like matrix non‐normality, provides a more complete description of the transient fluctuations than the damping ratio. Pseudospectra analysis could further support non‐normality assessment to enable a greater understanding of when we might expect transient phases to impact eventual population dynamics.